2014
DOI: 10.1038/oncsis.2014.29
|View full text |Cite
|
Sign up to set email alerts
|

PSGR promotes prostatic intraepithelial neoplasia and prostate cancer xenograft growth through NF-κB

Abstract: Prostate-specific G-protein-coupled receptor (PSGR), a member of the olfactory subfamily of G-protein-coupled receptors, is specifically expressed in human prostate tissue and overexpressed in prostate cancer (PCa). This expression pattern suggests a possible role in PCa initiation and progression. We developed a PSGR transgenic mouse model driven by a probasin promoter and investigated the role of PSGR in prostate malignancy. Overexpression of PSGR induced a chronic inflammatory response that ultimately gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…Recently, ORs came into the focus of drug development because ectopically expressed ORs were involved in physiological and pathophysiological mechanisms within human tissues, such as the chemotaxis of sperm, the proliferation of prostate cancer and liver cancer cells, the induction of wound-healing, the modulation of hepatic triglyceride metabolism, cytokinesis, apoptosis and the regulation of serotonin secretion [8, 13, 58, 60, 67, 79, 82, 90, 99, 108, 114]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, ORs came into the focus of drug development because ectopically expressed ORs were involved in physiological and pathophysiological mechanisms within human tissues, such as the chemotaxis of sperm, the proliferation of prostate cancer and liver cancer cells, the induction of wound-healing, the modulation of hepatic triglyceride metabolism, cytokinesis, apoptosis and the regulation of serotonin secretion [8, 13, 58, 60, 67, 79, 82, 90, 99, 108, 114]. …”
Section: Introductionmentioning
confidence: 99%
“…The β-ionone-dependent activation of OR51E2 resulted in a reduced proliferation of PCa cells via the Src-Pyk2- p38MAPK signaling pathway [45, 47, 48]. Controversy studies demonstrated prostate cancer growth promoting function of PSGR in vivo [49, 50]. Concomitantly, β-ionone stimulation even promotes LNCaP cell invasiveness in vitro and metastases spreading in vivo [49].…”
Section: Introductionmentioning
confidence: 99%
“…OR10J5 is expressed in the heart and is involved in angiogenesis27. Additionally, overexpressed OR51E2 (PSGR, prostate-specific G-protein-coupled receptor) enhanced oncogenesis in prostate tissue through activation of NF-κB28. However, the physiological roles of ORs in these tissues are still not well understood.…”
mentioning
confidence: 99%